A STATISTICAL ANALYSIS OF QUALITY CONTROL PROCESS ON PAPER PRODUCTION: A CASE STUDY OF BEL PAPYRUS LIMITED, OGBA, LAGOS STATE - Oseiwu, Ali Hassana; Obafemi, Orumbe Seth (International Journal For Research In Business, Management And Accounting, 2017)
This research is an analysis of quality control process on paper production on the soft roll production process of Bel Papyrus Ltd located in Ogba, Lagos State, Nigeria. The research was done with the aim of determining the conformity of the industry’s product to quality standard, identifying and eliminating the possible causes of variation in their production process, with reference to Percentage Elongation. The researchers used primary data in form of periodic laboratory test result done on soft rolls.Data presentations were made using simple statistical tools like Mean, Ranges, Standard Deviations, and Tables reflecting the primary data obtained at equal interval of production. The researchers made use of variable control charts for the purpose of analysis.